ASSOCIATION OF THYROID FUNCTION AND POST TRAUMATIC STRESS DISORDER: A SYSTEMATIC REVIEW - Prameswari, Pretika; Azhari , Ririn (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Numerous studies conducted over the last few decades have shown a negative correlation between post-traumatic stress disorder PTSD and physical health and wellbeing. Thyroid dysfunction may be related to a variety of mental disorders, including PTSD. However, it is still debatable. The aim: This study aims to investigate association between thyroid function and post-traumatic stress disorder. Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up to date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and ScienceDirect, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done. Results: In the PubMed database, the results of our search brought up 42 articles, whereas the results of our search on ScienceDirect brought up 163 articles. The results of the search conducted by title screening yielded a total 15 articles for PubMed and 10 articles for ScienceDirect. We compiled a total of 14 papers, 11 of which came from PubMed and 3 of which came from ScienceDirect. We excluded 3 review articles, 3 duplicate articles, 1 animal study, and 2 articles having ineligible outcomes data. In the end, we included five research that met the criteria. Conclusion: PTSD may alter thyroid function but there is scanty evidence regarding their relationship.